Biomimetic biomineralization nanoplatform-mediated differentiation therapy and phototherapy for cancer stem cell inhibition and antitumor immunity activation - Shan Gao; Meng Liu; Dongzhu Liu; Xinru Kong; Yuelin Fang; Yingying Li; Hang Wu; Jianbo Ji; Xiaoye Yang; Guangxi Zhai (Elsevier, 2023)
Growing evidence suggests that the presence of cancer stem cells (CSCs) is a major challenge in current tumor treatments, especially the transition from non-CSCs to differentiation of CSCs for evading conventional therapies and driving metastasis. Here we propose a therapeutic strategy of synergistic differentiation therapy and phototherapy to induce differentiation of CSCs into mature tumor cells by differentiation inducers and synergistic elimination of them and normal cancer cells through phototherapy. In this work, we synthesized a biomimetic nanoplatform loaded with IR-780 and all-trans retinoic acid (ATRA) via biomineralization. This method can integrate aluminum ions into small-sized protein carriers to form nanoclusters, which undergo responsive degradation under acidic conditions and facilitate deep tumor penetration. With the help of CSC differentiation induced by ATRA, IR-780 inhibited the self-renewal of CSCs and cancer progression by generating hyperthermia and reactive oxygen species in a synergistic manner. Furthermore, ATRA can boost immunogenic cell death induced by phototherapy, thereby strongly causing a systemic anti-tumor immune response and efficiently eliminating CSCs and tumor cells. Taken together, this dual strategy represents a new paradigm of targeted eradication of CSCs and tumors by inducing CSC differentiation, improving photothermal therapy/photodynamic therapy and enhancing antitumor immunity.